Relationship between bullies, victims and mental health issues among adolescent - Aishath Nasheeda; Che Hassan, Norlizah; Hassan, Siti Aishah (The Maldives National University, 2017)
The main purpose of this research is to examine the relationships between bullies, victims and mental health among adolescents in Maldives. The study investigates the types of bullying and victimization common among adolescent boys and girls. The study also investigate the types of mental health among adolescents in Maldives. Furthermore, this study investigates the moderating effects of gender and age on the relationship between bullies, victims and mental health among adolescents in Maldives. The research adopts a cross sectional quantitative survey method. Adolescents Peer Relation Inventory (APRI) for bullying and Mental Health Index (MHI38) were used as research instruments. A total of 460 survey questionnaires were analysed in this study. The target group of this study were adolescents between 11 to 16 years. Descriptive data were analysed using IBM SPSS version 22 and Structural Equation Modelling with AMOS were used to analysis the hypotheses. Findings suggest that verbal bullying is the most common type of bullying among males and females. Findings on victimization suggests that 85% of adolescents have been targets to all forms of bullying. The relationship between bullying others and mental health revealed a non-recursive relationship whereby, bullying others and mental health have significant negative relationship (-.96) and mental health and bullying others have a significant positive relationship (.96). Findings on moderating factors on the relationship revealed that age and gender does not moderate on this relationship. The study opens new doors for practitioners as well as policies makers on formulating positive interventions strategies such as engaging students in positive behaviours, peer counselling and nurturing empathy so that peers help each other in promoting healthy behaviour in school environment. The study looks through the lens of bio psychosocial model in order to provide insight into bullying. The study provides insight on understanding of the complexity of the life stressors that influence adolescents to engage as bullies and victims.